Diary of a Minecraft zombie : A scare of a dare. - Zombie, Zack. (Fictitious character) (New York : Scholastic, 2015)
A twelve-year-old Minecraft zombie shares what his life is really like.
3-6
4.1
Keywords: Diary -- Fiction; Zombies -- Fiction; Minecraft (Game) -- Fiction; Diary fiction; Video game characters; Video games